Thermal stabilisation of the short DNA duplexes by acridine-4-carboxamide derivatives. Issue 18 (26th September 2022) - Kostelansky, Filip; Miletin, Miroslav; Havlinova, Zuzana; Szotakova, Barbora; Libra, Antonin; Kucera, Radim; Novakova, Veronika; Zimcik, Petr
Abstract: The short oligodeoxynucleotide (ODN) probes are suitable for good discrimination of point mutations. However, the probes suffer from low melting temperatures. In this work, the strategy of using acridine-4-carboxamide intercalators to improve thermal stabilisation is investigated. The study of large series of acridines revealed that optimal stabilisation is achieved upon decoration of acridine by secondary carboxamide carrying sterically not demanding basic function bound through a two-carbon linker. Two highly active intercalators were attached to short probes (13 or 18 bases; designed as a part of HFE gene) by click chemistry into positions 7 and/or 13 and proved to increase the melting temperate ( T m ) of the duplex by almost 8°C for the best combination. The acridines interact with both single- and double-stranded DNAs with substantially preferred interaction for the latter. The study of interaction suggested higher affinity of the acridines toward the GC- than AT-rich sequences. Good discrimination of two point mutations was shown in practical application with HFE gene (wild type, H63D C > G and S65C A > C mutations). Acridine itself can also serve as a fluorophore and also allows discrimination of the fully matched sequences from those with point mutations in probes labelled only with acridine. Graphical Abstract: